Pelatihan Meronce Di Sdn 64/I Muara Bulian Untuk Meningkatkan Keterampilan Motorik Halus Siswa - Destrinelli,, Destrinelli; Hayati, Suci; Rosmalinda, Desy; Khoirunnisa, Khoirunnisa (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The lack of application of Meronce skills in learning is the reason why Meronce training has been implemented at SDN 64/I Muara Bulan. This is supported by observations that 80% of teachers at SDN 64/I Muara Bulian are not familiar with the Meronce technique, whereas the remaining 20% are aware of it but have not incorporated it into their teaching activities. The main reason for teachers' reluctance to implement Meronce activities in class is their ignorance of the benefits of this technique. In reality, there are many advantages of Meronce for students. It can help children develop their fine motor skills, which are crucial for writing. Meronce also teaches children to be attentive and focused, practice patience, and develop the ability to sort and match objects based on their color, shape, and size. The results of the PKM conducted at SDN 64/1 revealed that the training provided to teachers and lower-grade students was well-received and generated a positive response. This was evidenced by the participants' enthusiasm during the training.